(untitled) (Agroindustrial Science, 2026)
Fusarium wilt of banana (FWB), caused by Fusarium oxysporum f. sp. cubense (Foc), is a primary threat to Musa spp. Despite its impact, the intensity and potential drivers of the disease in the Peruvian Amazon remain poorly understood. This study assessed FWB prevalence, spatial distribution, and associated biophysical and management variables at the mesoscale. A census of 189 plots (213,005 mats) was conducted across six regions using visual inspection. Overall prevalence was 28.04%, with the highest value in Junín (55.56%). FWB was significantly associated with Isla (Iholena, AAB) and Seda (Gros Michel, AAA) cultivars. Spatial analysis revealed hierarchical aggregation with localized foci (radius = 13.8 km) and broader farm clustering at intermediate scales. Disease was more frequent in areas with higher altitudes (> 762.5 m a.s.l.) and annual precipitation (> 1481 mm). Higher flood risk zones, linked to pronounced rainfall seasonality, were identified as critical for pathogen movement via watercourses. FWB was identified as the main phytosanitary issue in affected areas, where the lack of intervention on symptomatic plants strongly correlated with disease presence.